إجراء تعليم اللغة العربية باستخدام الألعاب اللغوية بالمدرسة الإعدادية الحكومية 3 سابنج - Hayat, Almizanul (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2022)
All educational methods are based on the fact that the material cannot be taught properly except in a special way. One of the means in teaching the Arabic language is the use of language games. Language games are a new method in language education, and their applications have proven results in many countries that are interested in developing the teaching of their languages. Accordingly, the application of language games in teaching the Arabic language takes an important place because it depends on these two basics, namely play and joy. Language games are one of the methods used by the teacher in delivering study materials and have a major role in the success of students when learning. Based on these phenomena, the researcher wanted to search for linguistic games and use them to stimulate the students' desire to learn Arabic in the government preparatory school 3 Sabang. This research uses a procedural approach, which means that the researcher himself designs games directly in the field of research. The researcher found the results of the research, including that the design of language games and their use in teaching the Arabic language is good and effective.